AAFreqCoil: a new classifier to distinguish parallel dimeric and trimeric coiled coils1. Issue 7 (16th July 2015) - Wang, Xiaofeng; Zhou, Yuan; Yan, Renxiang
<x xml:space="preserve">Abstract</x> Coiled coils are characteristic rope-like protein structures, constituted by one or more heptad repeats.